Ryanodine Receptor-Mediated Calcium Release Has a Key Role in Hippocampal LTD Induction - Arias-Cavieres, Alejandra; Barrientos, Genaro C.; Sánchez, Gina; Elgueta, Claudio; Muñoz, Pablo; Hidalgo, Cecilia (Frontiers in Cellular Neuroscience, 2018)
The induction of both long-term potentiation (LTP) and long-term depression (LTD) of synaptic transmission entails pre- and postsynaptic Ca2+ signals, which represent transient increments in cytoplasmic free Ca2+ concentration. In diverse synapse types, Ca2+ release from intracellular stores contributes to amplify the Ca2+ signals initially generated by activation of neuronal Ca2+ entry pathways. Here, we used hippocampal slices from young male rats to evaluate whether pharmacological activation or inhibition of Ca2+ release from the endoplasmic reticulum mediated by ryanodine receptor (RyR) channels modifies LTD induction at Schaffer collateral-CA1 synapses. Pre-incubation of slices with ryanodine (1 µM, 1 h) or caffeine (1 mM, 30 min) to promote RyR-mediated Ca2+ release facilitated LTD induction by low frequency stimulation, but did not affect the amplitude of synaptic transmission, the profiles of field excitatory postsynaptic potentials (fEPSP) or the paired-pulse responses. Conversely, treatment with inhibitory ryanodine (20 µM, 1 h) to suppress RyR-mediated Ca2+ release prevented LTD induction, but did not affect baseline synaptic transmission or paired-pulse responses. Previous literature reports indicate that LTD induction requires presynaptic CaMKII activity. We found that 1 h after applying the LTD induction protocol, slices displayed a significant increase in CaMKII phosphorylation relative to the levels exhibited by un-stimulated (naïve) slices. In addition, LTD induction (1 h) enhanced the phosphorylation of the presynaptic protein Synapsin I at a CaMKII-dependent phosphorylation site, indicating that LTD induction stimulates presynaptic CaMKII activity. Pre-incubation of slices with 20 µM ryanodine abolished the increased CaMKII and Synapsin I phosphorylation induced by LTD, whereas naïve slices pre-incubated with inhibitory ryanodine displayed similar CaMKII and Synapsin I phosphorylation levels as naïve control slices. We posit that inhibitory ryanodine suppressed LTD-induced presynaptic CaMKII activity, as evidenced by the suppression of Synapsin I phosphorylation induced by LTD. Accordingly, we propose that presynaptic RyR-mediated Ca2+ signals contribute to LTD induction at Schaffer collateral-CA1 synapses.